2010
DOI: 10.1111/j.1365-2567.2009.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary role for d‐alanylated wall teichoic acid in Toll‐like receptor 2‐mediated survival of Staphylococcus aureus in macrophages

Abstract: SummaryWe previously reported that Staphylococcus aureus avoids killing within macrophages by exploiting the action of Toll-like receptor 2 (TLR2), which leads to the c-Jun N-terminal kinase (JNK)-mediated inhibition of superoxide production. To search for bacterial components responsible for this event, a series of S. aureus mutants, in which the synthesis of the cell wall was interrupted, were screened for the level of JNK activation in macrophages. In addition to a mutant lacking the lipoproteins that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Furthermore, the purification of specific serum IgGs recognizing these glycopolymers and the determination of their binding specificities to their ligands are difficult. Recently available S. aureus mutant strains that are deficient in cell-wall glycopolymers enable us to address the biological functions of S. aureus cell-wall components during host innate immune responses and pathogen infection in hosts (12,14,15,23). In this study, we confirmed the binding specificity of purified anti-WTA-IgG toward its ligand with S. aureus mutants deficient for WTA or LTA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the purification of specific serum IgGs recognizing these glycopolymers and the determination of their binding specificities to their ligands are difficult. Recently available S. aureus mutant strains that are deficient in cell-wall glycopolymers enable us to address the biological functions of S. aureus cell-wall components during host innate immune responses and pathogen infection in hosts (12,14,15,23). In this study, we confirmed the binding specificity of purified anti-WTA-IgG toward its ligand with S. aureus mutants deficient for WTA or LTA.…”
Section: Discussionsupporting
confidence: 70%
“…Purification of S. aureus WTA and LTA S. aureus WTA was purified as described previously (15). Because the phosphodiester linkage between WTA and N-acetylmuramic acid of monomeric-PGN is easily hydrolyzed by acid (16) (see Supplemental Fig.…”
Section: Protein Sera and Bacteriamentioning
confidence: 99%
“…Preparation of WTA from S. aureus-WTA was prepared from S. aureus strains according to our published method (32) with some modifications. Briefly, WTA-bound insoluble peptidoglycan was prepared and incubated with 5% trichloroacetic acid for 18 h at room temperature to release the WTA.…”
Section: Methodsmentioning
confidence: 99%
“…To remove WTA from peptidoglycan, this fraction was incubated in 40% (v/v) hydrofluoric acid at 4˚C for 18 h, and WTA-removed peptidoglycan was separated by centrifugation. WTA of S. aureus that retained D-alanine was prepared as described previously (9). Immune proteins of T. molitor and Tribolium castaneum were obtained as follows: Gram-negative bacteria-binding protein 1 (GNBP-1), a zymogen form of modular serine protease (MSP), and a zymogen form Spätzle-processing enzyme (SPE) were partially purified from the hemolymph of T. molitor larvae; T. molitor peptidoglycan recognition protein (PGRP)-SA, a zymogen form of T. molitor SPE-activating enzyme (SAE), and a proform of T. castaneum Spätzle were prepared as recombinant proteins using a baculovirus-based DNA vector and the insect cell line Sf9, as described previously (13).…”
Section: Bacterial Strains and Fly Stocksmentioning
confidence: 99%
“…This microbial action has been studied mainly with mammals, and several mechanisms have been proposed (1-7): a change to the structure of the cell surface to avoid recognition by sentinel immune cells or soluble factors; interference with signaling pathways for the production of proinflammatory cytokines and antimicrobial substances; inhibition of phagocytosis; and regulation of the maturation of phagosomes. Moreover, some microbes highjack the host innate immune system; Staphylococcus aureus exploits TLR2 to inhibit the production of superoxide in macrophages and evade killing after phagocytosis (8,9). This suggests that pattern recognition receptors and microbial components as their ligands operate two different reactions, one enhancing and the other mitigating host immunity.…”
mentioning
confidence: 99%